RISK ASSESSMENT KECELAKAAN KERJA PEMASANGAN BETON PRACETAK PADA PROYEK PEMBANGUNAN APARTEMEN DI SURABAYA - Reko Triyono; Noeroel Widajati (Universitas Airlangga, 2017)
Installation of precast concrete in construction of multi-storey buildings at risk of workplace accidents due to be carried out on the altitude. Installation of precast concrete must also use heavy equipment, because of the weight of the material to be install. Accidents on the installation of precast concrete can be very fatal and cause of death. Risk assessment is an attempt to calculating risk arising from hazards, take into account the adequacy of any existing controls, and deciding whether or not the risk is acceptable. The purpose of this research is to studies and perform risk assessment level onprecast concrete installation at apartment project in Surabaya with hazard, risk, risk control, and residual risk observation. Primary data were collected through interview and observation. Object of this research is installation proses of precast concrete wall at Puncak Bukit Golf Apartment project by PT. Wijaya Karya Bangunan Gedung in Surabaya. The data was analyzed descriptively using table and naration. Results showed that hazard identify in precast concrete installation at apartment project in Surabaya include: fall from height, squeezed, fallen object, struck by precast concrete, crush by precast concrete, and electro shock. Risk assessment has obtained 21 hazards. Risk control with was done: installing safety net for falling objects, safety induction, work instruction, wear PPE, and wear fall protection. The result of risk assessment showed19% risk are high risk, 38% with moderate risk category, and 43% with low risk category. Keywords: risk assessment, precast concrete, installing